Neural correlates of episodic memory in the Memento cohort. Issue 1 (22nd May 2018) - Epelbaum, Stephane; Bouteloup, Vincent; Mangin, Jean F.; La Corte, Valentina; Migliaccio, Raffaela; Bertin, Hugo; Habert, Marie O.; Fischer, Clara; Azouani, Chabha; Fillon, Ludovic; Chupin, Marie; Vellas, Bruno; et al.
Abstract: Introduction: The free and cued selective reminding test is used to identify memory deficits in mild cognitive impairment and demented patients. It allows assessing three processes: encoding, storage, and recollection of verbal episodic memory. Methods: We investigated the neural correlates of these three memory processes in a large cohort study. The Memento cohort enrolled 2323 outpatients presenting either with subjective cognitive decline or mild cognitive impairment who underwent cognitive, structural MRI and, for a subset, fluorodeoxyglucose–positron emission tomography evaluations. Results: Encoding was associated with a network including parietal and temporal cortices; storage was mainly associated with entorhinal and parahippocampal regions, bilaterally; retrieval was associated with a widespread network encompassing frontal regions. Discussion: The neural correlates of episodic memory processes can be assessed in large and standardized cohorts of patients at risk for Alzheimer's disease. Their relation to pathophysiological markers of Alzheimer's disease remains to be studied. Highlights: This is the largest cohort ever to be used in the study of the morpho‐metabolic correlates of episodic memory in human, ensuring the validity of the obtained results. We found that encoding of information is linked to a posterior network previously evidenced to support working memory. The storage process was mainly supported in our study by medial temporal regions. Spontaneous retrieval of stimuli implicated broad neural networks including the frontal regions. These associations were particularly strong in APOE ε4 carriers suggesting that the free and selective reminding test is useful to detect Alzheimer's disease at an early stage.